REDESIGNING USER INTERFACE OF TEMAN BUS APPLICATION USING GOAL-DIRECTED DESIGN - Yogi Putra Prastiawan; Veronikha Effendy; Anisa Herdiani (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2023)
In these modern era, it is very easy to create an investment portfolio, an investment portfolio can be formed by buying a shares. By creating portfolio investation, our can expect score return which makes it an advantage. However, there is also a risk value that will be obtained when buy shares. In the formation of an investment portfolio for active investors, it is expected to create an optimal investment portfolio, there are many models that can be used to create an optimal investment portfolio. In this final project, will discusses the use of the Black-Litterman Model in optimizing portfolios for active investors. The Black-Litterman model is one of the models that can be used to optimize the investment portfolio, the Black-Litterman model provides additional information for the return and risk values based on the views of experts. This model builds on the MV and CAPM using a Bayesian framework that allows investors to effectively incorporate their views of the market into the allocation process asset. Based on several tests that have been carried out during the research with different days, the value of the investor's view will always be different every day, the value of an optimistic view will have a good impact on the stock, even though the stock price is falling, if the investor's view is expressed optimism, the weight of the shares will remain high.